High expression of B7-H2 or B7-H3 is associated with poor prognosis in hepatocellular carcinoma - Zheng, Youshi (Mol Med Rep, 2019)
B7 family members have been associated with the signaling transduction pathways underlying tumor immune evasion in hepatocellular carcinoma. In the present study, associations between the clinical characteristics of patients with hepatocellular carcinoma (HCC) and the expression of B7-H2 and B7-H3 were analyzed. A total of 63 formalin-fixed and paraffin-embedded HCC tissues were collected to be used as a tissue microarray. Following this, the association between B7-H2/B7-H3 and the prognosis of patients with HCC was analyzed using Pearson's χ(2) test, the Kaplan-Meier method and receiver operating characteristic curve analysis. The results demonstrated that the expression of B7-H2 was significantly associated with recurrence (within 1 year) in patients with HCC (P<0.01), and that the expression of B7-H3 was associated with recurrence (within 1 year), metastasis and 2-year overall survival rate in patients with HCC (P<0.01, P=0.036 and P=0.016, respectively). In addition, the combined expression of B7-H2 and B7-H3 was associated with prognostic factors, including recurrence (within 1 year) and survival rate (within 2 years), in patients with HCC. In particular, an increased area under the curve was achieved when the combined expression of B7-H2 and B7-H3 was considered, compared with that for α-fetoprotein. Taken together, these results indicated that B7-H2- and/or B7-H3-positive expression indicates a poor clinical outcome for patients, and the combination of B7-H2 and B7-H3 may be a preferential prognostic biomarker in patients with HCC.